2011
DOI: 10.1371/journal.pone.0018128
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic Acid Is an Eph-ephrin Ligand Interfering with Eph-kinase Activation

Abstract: Eph-ephrin system plays a central role in a large variety of human cancers. In fact, alterated expression and/or de-regulated function of Eph-ephrin system promotes tumorigenesis and development of a more aggressive and metastatic tumour phenotype. In particular EphA2 upregulation is correlated with tumour stage and progression and the expression of EphA2 in non-trasformed cells induces malignant transformation and confers tumorigenic potential. Based on these evidences our aim was to identify small molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 36 publications
2
91
0
Order By: Relevance
“…The synthesized compounds 5e21 were evaluated for their ability to disrupt the binding of biotinilated-ephrin-A1 to the EphA2 receptor, using a previously validated ELISA binding protocol [17]. The pIC 50 values for the newly synthesized compounds are reported in Table 1, together with the corresponding standard error of the mean (SEM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized compounds 5e21 were evaluated for their ability to disrupt the binding of biotinilated-ephrin-A1 to the EphA2 receptor, using a previously validated ELISA binding protocol [17]. The pIC 50 values for the newly synthesized compounds are reported in Table 1, together with the corresponding standard error of the mean (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, derivatives of lithocholic acid (compound 1, Fig. 1) were discovered as competitive and reversible antagonists of the EphA2 receptor [16], active in prostate cancer [17] and cardiac muscle cells [18] at non-cytotoxic concentration. Other small molecules interfering with the Epheephrin system reported so far include i) 4-(2,5-dimethyl-1H-pyrrol-1-yl)-2-hydroxybenzoic acid (also know as CPD-1, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…29 To perform binding assays, all of the compounds were dissolved in PBS as 1 mM stock solution and immediately tested to assess their interference with EphA2−ephrinA1 binding as previously described. 22 Briefly, the EphA2-Fc ectodomain was immobilized on ELISA plates (Corning 9018), and binding of biotinylated-ephrin-A1-Fc was detected using a standard colorimetric reaction developed by streptavidin−HRP and tetramethylbenzidine. Selectivity and specificity of the assay were previously assessed using nonbiotinylated ephrinA1-Fc as a ligand of the EphA2-Fc receptor.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Furthermore, Fc alone (AG714, Millipore) did not interfere with the binding process in the range of concentrations tested. 22 All of the compounds were tested three times, incubating at 100 μM for 1 h before the addition of biotinylated ephrinA1-Fc at a concentration corresponding to its K D (100 ng/mL) (Figure 2A). Compounds displacing >40% binding, namely, gallic acid, 3′,4′-dihydroxyphenylacetic acid, protocatechuic acid, pyrogallol, and pyrocatechol, were further studied to calculate the inhibitory concentration that reduced binding by 50% (IC 50 ).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Another study has found lithocholic acid as a reversible competitive inhibitor of EphA2, which inhibits ephrin binding to several Eph receptors and subsequent receptor tyrosine phosphorylation (64). Although Eph receptor signaling in tumor cells often appears to be ligand-independent, interfering with ligand-receptor interactions may suppress tumor angiogenesis and signaling in the other components of the tumor microenvironment.…”
Section: Small Molecular Antagonists or Agonists Of Eph Receptormentioning
confidence: 99%